2022
DOI: 10.1029/2021gc010308
|View full text |Cite
|
Sign up to set email alerts
|

Combined Nitrogen‐Isotope and Cyclostratigraphy Evidence for Temporal and Spatial Variability in Frasnian–Famennian Environmental Change

Abstract: The Upper Kellwasser (UKW) Event featured one of the "Big Five" Phanerozoic mass extinctions, during the Frasnian-Famennian (FF) transition (∼372 Ma), alongside worldwide environmental disturbances (see Carmichael et al., 2019). The event began ∼150 kyr prior to the end of the Frasnian Stage (De Vleeschouwer et al., 2017),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 94 publications
(251 reference statements)
2
9
0
Order By: Relevance
“…In our samples, isorenieratane and paleorenieratane are not detected (expected when T max ≥ 438°C; Requejo et al, 1992), but the δ 13 C values of aryl isoprenoids are more positive relative to those of algae‐derived, short‐chain n ‐alkanes (Figure 6), confirming that aryl isoprenoids were produced via the reductive tricarboxylic acid (TCA) cycle used by Chlorobium (Koopmans et al, 1996; Summons & Powell, 1987). Previous studies of the F‐F strata from the Illinois Basin and neighboring Appalachian Basin detected both aryl isoprenoids and isorenieratane, supporting green sulfur bacteria as the biological source of isoprenoids (Haddad et al, 2016, 2018; Percival et al, 2022). The highly variable but overall elevated TOC‐normalized aryl isoprenoid concentrations through the extinction interval (Figure 4) indicate a more intensive photic euxinia zone (PZE) in the Illinois Basin.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…In our samples, isorenieratane and paleorenieratane are not detected (expected when T max ≥ 438°C; Requejo et al, 1992), but the δ 13 C values of aryl isoprenoids are more positive relative to those of algae‐derived, short‐chain n ‐alkanes (Figure 6), confirming that aryl isoprenoids were produced via the reductive tricarboxylic acid (TCA) cycle used by Chlorobium (Koopmans et al, 1996; Summons & Powell, 1987). Previous studies of the F‐F strata from the Illinois Basin and neighboring Appalachian Basin detected both aryl isoprenoids and isorenieratane, supporting green sulfur bacteria as the biological source of isoprenoids (Haddad et al, 2016, 2018; Percival et al, 2022). The highly variable but overall elevated TOC‐normalized aryl isoprenoid concentrations through the extinction interval (Figure 4) indicate a more intensive photic euxinia zone (PZE) in the Illinois Basin.…”
Section: Discussionmentioning
confidence: 73%
“…Our observation is consistent with PZE biomarkers extensively detected in strata from Late Devonian epicontinental seas and basins worldwide, including Europe, North America, South America, and Africa (Lu, Lu, Ikejiri, Sun, et al, 2021), although the onset, tempo, and magnitude of PZE appear to vary spatially. For example, Percival et al (2022) reported a concentration peak of isorenieratane below the F‐F boundary in the Kowala section (Poland) and a smaller peak at the F‐F boundary in a drill core from the Illinois Basin (Iowa). Lu, Lu, Ikejiri, Sun, et al (2021) observed that the variation in PZE biomarkers from the Appalachian Basin exhibited precession‐driven cyclicity during the UKW.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations